Keterkaitan Sisi Negatif Era Milenial Dengan Ramalan Keadaan Kali Yuga - I Dewa Gede Darma Permana (Satya Widya: Jurnal Studi Agama, 2020)
Abstract Speaking about the Millennial era today, will not be separated from the term generation Millennial generation ages productive with typical born in the world with the development of science and technology has been growing rapidly. In the teachings of Hinduism itself, the present period is referred to as, a term of Kali Yuga the dark ages which is estimated to have started about 5000 years ago. In the age of Kali, the condition of the world was no longer certain, full of chaos, and the application of religious teachings only received a modest portion. So, mankind, especially the younger generation at this time, began to forget God because it was considered taboo. If we look at it more deeply, the Millennial era goes hand in hand with the Kali Yuga that is happening now. From this, looking at the Millennial era perspective to understand it more deeply from the perspective Vedic as a way of life for Hindus is the subject of this paper. This is done by searching for literature related to this with the aim of finding a link between the development of technology use in the Millennial era and the dark nature of Kali Yuga. Keyword: Millennial Era, Vedic, Kali Yuga